Roadmap towards optimal magnetic properties in L10-MnAl permanent magnets. (15th February 2023) - Jia, Yuxiao; Wu, Yuye; Xu, Yichen; Zheng, Ruixiao; Zhao, Shiteng; Skokov, Konstantin P.; Maccari, Fernando; Aubert, Alex; Gutfleisch, Oliver; Wang, Jingmin; Wang, Hui; Zou, Jianxin; et al.
Abstract: Twin boundaries impact negatively the magnetic properties in conventionally-fabricated L10 -type and RETM12 -type permanent magnets. Herein, we propose a strategy to suppress twins' formation by decreasing the grain and/or particle sizes below a critical size of D t ∼300 nm in L10 -MnAl permanent magnets, thereby relieving twinning-inducing stress by shifting the balance between volume and surface energy. Twin-free monocrystalline nanoparticles smaller than D t were used for preparing field-aligned polymer-bonded magnets with high texture. Generalizing our research findings, we propose here a roadmap for selecting the best route for manufacturing high-performance MnAl magnets, depending on their grain / particle size. The dependence of coercivity on grain/particle sizes shows that optimal coercivity can be reached within the range of 50–200 nm, which also shows a pathway to achieve the twin-free microstructure allowing the achievement of high texture degree in polymer-bounded or sintered magnets textured in a magnetic field. The results reported here can be applied to other twin-containing permanent magnet compounds, offering opportunities to drastically increase their texture and maximal energy products. Graphical abstract: Image, graphical abstract